Witness and Evangelism - Mark R. Teasdale (St Andrews Encyclopaedia of Theology, 2023)
Witness and evangelism are concepts related to how Christians participate in the mission of the triune God (missio Dei). As stated in Together Toward Life, a document published by the World Council of Churches Commission on World Mission and Evangelism (CWME), God’s mission is to share the fullness of life with all creation. God initially shared this life through the act of creation. When humanity rejected life by choosing to sin, God’s mission remained unaltered, with the Father sending the Son and the Spirit to make the fullness of life available to creation again. God’s central act to overcome death and restore life was the incarnation of the Son in Jesus of Nazareth, culminating in Jesus’ crucifixion and resurrection. So all people would be aware of God’s work through Jesus, Jesus commissioned his disciples to share the good news (or gospel) that abundant life is available through God’s grace given through Jesus Christ. Christians become witnesses for Jesus and practitioners of evangelism by communicating the gospel to others and inviting them to receive abundant life by likewise becoming disciples of Jesus (Ekué and Longkumer 2012: 57–58). The term witness can be used as both a noun and a verb. As a noun, it refers to one who testifies about something they have first-hand knowledge of so that others might believe in the message they share. This idea is expressed in the prologue of 1 John: ‘We proclaim to you what we have seen and heard, so that you also may have fellowship with us. And our fellowship is with the Father and with his Son, Jesus Christ’ (1 John 1:3). God can empower anyone or anything to be a witness. This includes individual Christians, groups of Christians, the church collectively, the Holy Bible, nature, or anything else God works through to reveal the gospel and invite others to respond. As a verb, ‘witness’ describes the wide array of activities that Christians can engage in to share the abundant life of God with others. For example, Christians can witness to the gospel through the arts, humanitarian aid, education, healthcare, acts of justice, liturgical practices, or explaining the biblical narrative. Each of these acts can extend a portion of the abundant life of God to others and, by doing so, demonstrate God’s love for creation. Evangelism is the central act of witness. As the CWME states,